The die is cast: Sweden and Finland’s long road to NATO - E. V. Korunova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The accession of Sweden and Finland to NATO came as a shock to many politicians and experts, who until the last moment had believed that these two states would not renounce their traditional neutrality policy. The surprise effect was further enhanced by a remarkable coherence of the countries’ approaches to their membership in the alliance. In order to provide a better understanding of this fundamental shift in Sweden and Finland’s foreign policy courses, this paper examines the evolution of their policies of neutrality during the tribulations of the Cold War. The first section considers the formation of the non-aligned strategies of Finland and Sweden in the aftermath of World War II, which took the form of the so-called Paasikivi-Kekkonen and Unden doctrines, respectively. The author emphasizes that, despite the formal resemblance, the approaches of Sweden and Finland to the neutrality policy varied substantially, since their ambitions and aspirations, as well as their role in the emerging bipolar order were also very different. However, the two states had tended to coordinate their foreign policies already back then and this trend only strengthened in the following decades of the Cold War. The second section shows how the Finnish neutrality model, initially focused on building special relations with the USSR, and a more flexible Swedish non–aligned policy, facilitated convergence of the two states, as well as their cooperation with the Nordic members of NATO. The third section outlines the determinants of the foreign policy transformation of the Northern European neutrals in the aftermath of the Cold War. The author notes that it was the collapse of the bipolar order that paved the way for the comprehensive engagement of Finland and Sweden in the activities of the alliance. It is shown that apart from this cooperation with NATO, a number of regional initiatives involving the Nordic and Baltic countries strengthened foreign policy coordination and contacts between Finland and Sweden. The formal accession of both to NATO thus became only the end point of these processes and the result of the conscious refusal of these countries’ leadership from the original and time-tested non-alignment policy. The consequences of this decision have yet to be assessed by politicians and experts, but one its immediate effect is clear — the emergence of a new security dilemma for the countries of the region.